Field evaluation of an unmanned aerial vehicle (UAV) sprayer: effect of spray volume on deposition and the control of pests and disease in wheat. Issue 6 (14th February 2019) - Wang, Guobin; Lan, Yubin; Qi, Haixia; Chen, Pengchao; Hewitt, Andrew; Han, Yuxing
Abstract: BACKGROUND: Unmanned aerial vehicles (UAVs) are a recently developed aerial spraying technology. However, the effect of spray volume variation on deposition and pesticide control efficacy is unknown. The effect of three UAV spray volumes (9.0, 16.8 and 28.1 L ha −1 ) using three different nozzle sizes on droplet deposition and wheat aphid and powdery mildew control efficacy was assessed. An electric air‐pressure knapsack (EAP) sprayer was used as a comparison. RESULTS: Different spray volumes significantly influenced the deposition and control efficacy of the UAV and EAP. For the UAV, a low spray volume of 9.0 L ha −1 with a fine nozzle (nozzle LU120‐01) resulted in lower deposition and control efficacy. Optimal control efficacy was achieved with coarser nozzles (nozzles LU120‐02, ‐03) at > 16.8 L ha −1 volume with systemic insecticide, and at 28.1 L ha −1 with contact insecticide and fungicide. For EAP, a high spray volume led to run‐off, and a spray volume of 225 L ha −1 achieved better deposition and control efficacy. CONCLUSION: The UAV had comparable deposition and efficacy control to the EAP at a higher spray volume (> 16.8 L ha −1 ) with coarse nozzles, but exhibited inferior deposition and efficacy control at a lower spray volume (<9.0 L ha −1 ) with fine nozzles. © 2019 Society of Chemical Industry Abstract : This article explored the feasibility of pesticide application using a new application method, an unmanned aerial vehicle, and studied the effect of spray volume on pesticide deposition and control efficacy of pests and disease in wheat.